Pattern of Etiologies of Early Neonatal Mortality in Tertiary Care Hospital, Peshawar - Lal Muhammad; Hina Pervaiz; Afzal Khan; Bakhat Beland; Inayat ullah (Life and Science, 2024)
Objective: To identify the pattern of etiologies responsible for the early neonatal mortality in neonates admitted in the neonatal intensive care unit. Study Design: Comparative cross-sectional study. Place and Duration of Study: This study was conducted in Neonatal Intensive Care, Lady Reading Hospital, Medical Teaching Institute Peshawar, Pakistan from September 2023 to January 2024. Methods: Data was collected for both groups according to sample size and parents were interviewed through Semi semi-structured questionnaire at the time of expiry. Through SPPS 27, data analysis was performed for quantitative and qualitative variables. Chi-square test was performed and then Binary logistic regression was performed taking outcome as the dependent variable. Results: The estimated neonatal mortality for our study was 25.5%. The mean age at the time of admission was 2.69 days±1.75. Overall females were 19.2% and male neonates were 80.8%. Neonatal mortality was significantly associated with the age of the mother, mode of delivery, sepsis, preceding birth interval in months, antenatal clinic visits in pregnancy, mother's education, father's education, and wealth index. The age of the mother had a significant relation with neonatal mortality age <16 years caused 9.9 times higher mortality when compared with the reference category. Considering the antenatal visits during pregnancy, no antenatal visit is 4.5 times more associated with mortality. Similarly, maternal illiteracy had a significant impact on mortality with an odds ratio of 3.6. The short preceding birth interval was significantly associated with neonatal mortality with an odds ratio of 2.8 on multivariate analysis. Conclusion: The findings of this research depict an association between early neonatal mortality and various factors including the mother's age, preceding birth interval, antenatal clinic visits during pregnancy, mother's and father's education, and wealth index of the family.